Influence of Rock Properties in Estimating Rock Strength for Shallow Underground Structures in Weak Rocks - Agustawijaya, Didi Supriadi (Indonesian Journal on Geoscience, 2018)
DOI: 10.17014/ijog.5.2.93-105Two popular rock strength criteria, the linear Coulomb and non-linear Hoek-Brown, are widely used in underground designs. These two criteria may be applied differently depending on rock conditions. Weak rocks may have different properties compared to hard rocks. Both criteria have been applied in a current research to practically determine the applicability of the criteria in estimating the strength of weak rock masses of five shallow underground structures. Results show that both criteria are able to model the strength of the five weak rock masses, but as expected the criteria provide quite different values for each type of rocks. The strength of rock masses around underground structures depends on uniaxial compressive strength and confinement; but the linear criterion very much depends on shear characteristics of rock materials. Whereas, the non-linear criterion relies on the geological strength index (GSI). Although the GSI may have served practical descriptions for rock masses, some difficulties were found when using the GSI for very weak pyroclastic rocks. The GSI seems to provide underestimated indexes for these rock types. Estimations show that the non-linear criterion may not really exhibit curved strength envelopes rather linear in some sense, for five weak rock masses. Thus in general, when an underground structure is reasonably shallow, has a lack of confinement, and where the shear behaviour dominates rock failures, the linear criterion is more preferable than the non-linear criterion in modelling the strength of weak rock masses.